Case report: Use of laparoscopic electrocoagulation rods in endovenous thermal ablation of saphenous trunks in the treatment of varicose veins of the lower extremities - Wang, Ling; Wang, Ya; Niu, Xiaoyang; Lv, Zhengzuo; Wang, Bing (Frontiers in Surgery, 2023)
Varicose veins of the lower extremities are a very common condition in vascular surgery. With advances in technology and medicine, minimally invasive endovenous thermal ablation has become the primary approach used to treat patients with moderate or severe varicose veins. Electrocoagulation for thermal ablation is a relatively simple and economical procedure, but standards vary according to location and some limitations exist. We report a case of a 58-year-old female patient with small saphenous varicose veins in the right lower extremity in which an electrocoagulation rod commonly used in laparoscopic surgery was innovatively used instead of a standard variable electrocoagulation device. The venous clinical severity score was used to assess changes in clinical symptoms before and 3 months after the procedure. The procedure was shown to have eliminated venous reflux, improved the patient's clinical symptoms, and venous function. This procedure may be a reliable option for future endovenous electrocoagulation thermal ablation procedures for varicose veins that are simple and convenient to perform.